FEASIBILITY TEST ANALYSIS OF MINIMUM COMPETENCY ASSESSMENT (AKM) ISLAMIC RELIGIOUS EDUCATION SUBJECTS ON MARRIAGE USING THE RASCH APPROACH - Islamaya, Yasinta; Putranta, Himawan (Yayasan Sukma, 2025)
The Ministry of Education and Culture's policy in regulating education in Indonesia issued an independent learning education policy consisting of four points, namely, the National Standardized School Examination (USBN) was abolished, which then returned the program to each school's policy and the National Examination (UN) was replaced by the Minimum Competency Assessment (AKM) assessment and character survey. The implementation of AKM aims to improve reading, writing, and math skills. To support government policies to produce quality AKM questions, this study aims to analyze the feasibility test of AKM questions in PAI subjects on marriage material. This study discusses the analysis of validity, reliability, distractor function, and item difficulty using descriptive quantitative methods with the Rasch approach by utilizing Ministep Rasch software. The AKM questions are multiple-choice questions totaling 10 items, five literacy items, and five numeracy items with four alternative answers, distributed to 30 respondents. Respondents consisted of students of PAI and its allied study programs. The results of this study's analysis indicate that eight items meet the requirements of the empirical validity test. At the same time, 2 of them are not appropriate, but overall the items are valid.